ETIKA MENDIDIK ANAK DALAM PANDANGAN AGAMA KRISTEN BERDASARKAN AMSAL 19:18 - Neti Pera Br. Berutu; Bobby Lumbantobing (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The character of a child is of utmost importance in social life because it manifests in every behavior in daily life. This research aims to understand the ethics of child education from a Christian perspective, specifically related to Proverbs 19:18. Education is a fundamental foundation for all humans, one aspect of which is "ethics," which involves instilling moral ethics from an early age. Children must be educated and encouraged to apply all the noble values as taught by the Word of God and be kept away from all forbidden things. The research method used is a literature review, which involves identifying relevant research topics, searching for sources from the Bible, books, and academic journals, selecting sources based on accuracy and relevance criteria, collecting data from the chosen sources, thoroughly evaluating the validity and authority of each source, conducting a comprehensive analysis of the collected data, interpreting the research results to uncover patterns and trends, drafting a clear and structured report, and reporting and publishing the findings. An important finding in this study is that parents must possess quality spirituality and be skilled in educating their children in the Lord. Additionally, the grace of God, willingness, and self-discipline are required to continuously enhance spiritual growth.